Kejadian Perdarahan Pemasangan Nasogastric Tube Pada Pasien Anak Dengan Trombositopenia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Background: Thrombocytopenia is the abnormal count of the thrombocyt under 150.000mm3. The problem of thrombocytopenia is gastrointestinal tract bleeding. One of the factors is able to improve risk of bleeding occurrence of Nasogastric Tube (NGT) installation at children with thrombocytopenia. Objective: To know bleeding occurrence of NGT installation, bleeding occurrence of NGT installation with or without thrombocyte transfusion and bleeding manifestation of NGT installation at children with thrombocytopenia. Method: Non experimental with retrospective approach through observation of medical record study of children with thrombocytopenia from 1" January until 31 December 2004. Amount of sample counted 80 patients with thrombocytopenia and analyzed with 2x2 tables Chi Square Test. Result: Children with thrombocytopenia which attached NGT 20 were (25%). The total of bleeding occurrence of nasogastric installation counted 4, Occurrence of majority thrombocytopenia at 1-5 years old were 38 (47,5%) and at cancer diseases like leukemia disease were 32 (40%). Conclusion: Children with thrombocytopenia which attached by NGT had experienced two times bleeding risk compared to other which hadn't attached. Children with trombocyte count lees than 70.000 mm3 had 2,07 times risk of bleeding compared with children who had more. Children who didn't have trombocyte transfusion had 2,67 times bleeding risk compared with children who had. From the total bleeding occurance of NGT installation